PENGARUH TINGKAT PENDIDIKAN, PEKERJAAN DAN PENDAPATAN KELUARGA YANG MENDAPAT PENDIDIKAN KESEHATAN TERHADAP PERILAKU DETEKSI DINI KANKER LEHER RAHIM DI DESA BANTUL KECAMATAN BANTUL DIY - Muryani Muryani (STIKES Wira Husada Yogyakarta, 2016)
ABSTRACTBackground: The inﬂ uence of educational level, occupation and income of health service recipients on early detection to preliminary cervical cancer in family.Objective: Early detection of cervical cancer is vital to discover the possibility of occurrence in later stage. Late in detecting could result in metastasis of cancer around other vital organs that subsequently can cause complication. Education of health, cooperation between patients, family and professional medics is therefore necessary. The aim of this research is to discover the inﬂ uence of educational level, occupation and income of health service recipients on early detection of cervical cancer in family. Method of the research is descriptive analytic with cross-sectional approach. The research was conducted in February 2015. Target population covers family with mothers who own children in Bantul village. Sampling is based on purposive sampling, resulting in as many as 60 respondents. Data collection relies on questionnaire. Data analysis uses Chi-square; meanwhile to process all variables logistic-binary regression analysis is employed along with SPSS program version 12. Method the result of the research shows that high education can provide 3,4 times more early detection on cervical cancer in family, better than lower education. Other factors inﬂ uencing the attitude of early detection of cervical cancer in family are occupation and income.Conclusion: the research concludes that level of education; occupation and income are the determining factors in early detection of cervical cancer in family.